2021
DOI: 10.1021/acs.jpcc.1c07371
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Addition of Desired Carboxylate Ligands to CdSe Quantum Dots Passivated with Phosphonic Acids

Abstract: Phosphonic acids bind strongly to quantum dots (QDs), improving stability. However, it is difficult to introduce desired ligands to QDs passivated with phosphonic acids via ligand exchange. Here, we have investigated the efficient addition of X-type ligands to wurtzite CdSe QDs passivated with phosphonic acids using Z-type ligands. Oleic acid (OA) and Cd­(OA)2 were used as examples of the desired X-type and Z-type ligands, respectively, and octadecylphosphonic acid (ODPA) was used as a passivating ligand for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…It is interesting to look at the quantification of all free and bound species during the titration (Figure C,F). The amounts of free (released) phosphinic acid and the bound phosphonate are equal (within error) over the course of the titration, indicating again a one-for-one exchange, which is consistent with the previous literature on phosphonate ligand binding. ,, There is an exception for smaller clusters since a two-for-one exchange was observed on InP clusters . Interestingly, our exchange reaction does not go to completion, and the bound phosphinate saturates at 40 and 30% for HfO 2 and CdSe, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is interesting to look at the quantification of all free and bound species during the titration (Figure C,F). The amounts of free (released) phosphinic acid and the bound phosphonate are equal (within error) over the course of the titration, indicating again a one-for-one exchange, which is consistent with the previous literature on phosphonate ligand binding. ,, There is an exception for smaller clusters since a two-for-one exchange was observed on InP clusters . Interestingly, our exchange reaction does not go to completion, and the bound phosphinate saturates at 40 and 30% for HfO 2 and CdSe, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Not surprisingly, an equilibrium is observed for different ligands with the same binding group, for example, carboxylate ligands are in equilibrium with most other carboxylic acids. Interestingly, the driving force for X-type ligand exchange in nonpolar solvents is often the proton transfer from the incoming proligand to the surface-bound ligand . In non-polar solvents, carboxylate ligands (p K a ≈ 4.75) are quantitatively exchanged for a stronger acid such as phosphonic acid (p K a ≈ 1.1–2.3), , trifluoroacetic acid (p K a ≈ 0.5), or hydrochloric acid (p K a ≈ −8) . The reverse reaction (e.g., chloride replaced by carboxylate) is observed when a base (e.g., an alkylamine) is added. ,, Under such basic conditions, the proton transfer is no longer part of the ligand exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium phosphonate was exchanged for cadmium oleate, to some extent, on the surface of CdSe nanocrystals. 82 Addition of oleic acid to cadmium phosphonate capped nanocrystals did not result in any exchange, as expected.…”
Section: Kinetics Of Ligand Exchangesupporting
confidence: 75%
“…Previous studies have suggested that CdSe ligand surface coverages up to ca. 2–4 ligands per nm 2 depending upon the ligand footprint. ,, For a 5 nm CdSe QD in contact with a planar oxide with a surface linker coverage of ca. 10 –10 moles/cm 2 , as few as 3–6 linkages per QD are expected, but as many as ca.…”
Section: Resultsmentioning
confidence: 99%